Sympterygia bonapartii, Smallnose Fanskate - Pollom, R. (2020)
The Smallnose Fanskate (Sympterygia bonapartii) is a medium-sized (to 88 cm total length) skate that occurs in the Southeast Pacific in the Strait of Magellan, Chile, and in the Southwest Atlantic from Rio de Janeiro, Brazil to Santa Cruz, Argentina. It is demersal on the continental shelf and upper slope and inhabits depths down to 100 m and occasionally to 500 m deep. This skate is captured in intense artisanal and commercial demersal trawl and longline fisheries and recreational fisheries in Argentina. Research trawl surveys conducted on the southern Brazilian shelf indicate a reduction in catch-per-unit-effort (CPUE) of 94% between 1980 and 2005. In Uruguay, research surveys exhibit an increase in catch-per-unit-effort between 1984 and 2008 followed by a stabilization. Overall, the Smallnose Fanskate is subjected to intense largely unregulated fishing pressure across most of its range, but is able to survive when discarded. The larger part of this species' range is in central and southern Argentina where fishing mortality is likely to be lower. Due to the level of fisheries mortality that this species is exposed in the northern part of its range, balanced with lower pressure in the south, and its high survivorship when discarded, it is suspected that the Smallnose Fanskate has undergone a population reduction of 20-29% over the past three generations (49.5 years), and it is assessed as Near Threatened (nearly meeting Vulnerable A2bd).